Drug and therapeutics committee interventions in managing irrational drug use and antimicrobial stewardship in China - Yang, Jing; Zheng, Lei; Guan, Yu-Yao; Lv, Yong-Tao (Frontiers in Pharmacology, 2022)
Aim: This study aimed to describe the key points in the transformation of the functions of the Drug and Therapeutics Committee (DTC) of the Shandong Provincial Third Hospital and how to provide full authority to its role in the control of rational drug use, especially in the management of antibiotic use. Method: The DTC was restructured and three working groups were established: the prescription review management group, the antimicrobial stewardship group, and the rational drug use service group. From January 2016 to December 2021, each group played a role in promoting rational drug use and antimicrobial stewardship. In addition, we performed statistics on typical management cases, irrational drug use, bacterial resistance rate, and drug costs from 2015 to 2021 to evaluate the effect of management by the DTC. Results: Intervention by the DTC led to a significant reduction in prescribing errors (71.43%, P < 0.05), the intervention acceptance rate increased by 16.03%, and the problem solved rate increased by 32.41% (P < 0.05). Resistance rates of general spectrum antibiotics were reduced remarkably after the intervention. The quality of drug treatment was improved and patient drug expenses was continuously reduced. Conclusions: Giving full play to the functions of the DTC can significantly improve the level of drug treatment and reduce unreasonable drug use to save unnecessary drug expenses and slow the development of drug resistance.